2011
DOI: 10.1097/sla.0b013e3182196ff4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sacral Nerve Modulation on Cerebral Evoked Potential Latency in Fecal Incontinence and Constipation

Abstract: Measurement of P40 latency of SEP at baseline and at 1 month of SNM at a frequency of 40 Hz may help to predict the outcome of SNM and thus influence the decision for permanent implantation for patients with incontinence and constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 21 publications
1
52
0
1
Order By: Relevance
“…This is supported by evidence of altered motility in the right side of the colon during SNS [11,12]. Furthermore, SNS alters cerebral evoked potentials and reduces the overall corticoanal excitability during rectal distension [9,24]. Thus, modulation through afferent nerve fibres may be an important part of the mode of action of SNS for IBS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is supported by evidence of altered motility in the right side of the colon during SNS [11,12]. Furthermore, SNS alters cerebral evoked potentials and reduces the overall corticoanal excitability during rectal distension [9,24]. Thus, modulation through afferent nerve fibres may be an important part of the mode of action of SNS for IBS.…”
Section: Discussionmentioning
confidence: 93%
“…Based on results from the same patient group, we have previously reported that SNS alleviates IBS specific symptoms including pain, bloating, diarrhoea, constipation and satiety and that the effect lasts at least one year [7]. In patients with faecal incontinence, the percutaneuos nerve evaluation test alters rectal sensation to distension [9,24,25]. Most IBS patients have visceral hypersensitivity [26,27] and abnormal engagement of CNS regions associated with emotional arousal and endogenous pain modulation has been documented during rectal distension [28].…”
Section: Discussionmentioning
confidence: 99%
“…3. FIQL score changes before and after the treatment higher perception of afferent information (36,37). However, no anorectal physiological changes are consistently observed from PTNS and SNS (38).…”
Section: Discussionmentioning
confidence: 97%
“…3 The results of this trial confirmed the salutary effects of the therapy as had been repeatedly demonstrated in European and Australian trials. [4][5][6][7][8] The other alternatives for the treatment of FI including traditional overlapping sphincteroplasty, 9 graciloplasty, 10-14 artificial bowel sphincter 15-16 and stoma construction will all continue to play roles in our therapeutic algorithms. In addition, some recent studies have demonstrated reasonable results with injectables 17-18 although limited long term data are available to recommend their use.…”
mentioning
confidence: 99%